An LRR-domain containing protein identified in Bathymodiolus platifrons serves as intracellular recognition receptor for the endosymbiotic methane-oxidation bacteria. Issue 93 (October 2019) - Chen, Hao; Wang, Minxiao; Zhang, Huan; Wang, Hao; Lv, Zhao; Zhou, Li; Zhong, Zhaoshan; Lian, Chao; Cao, Lei; Li, Chaolun
Abstract: As domain species in seep and vent ecosystem, Bathymodioline mussels has been regarded as a model organism in investigating deep sea chemosymbiosis. However, mechanisms underlying their symbiosis with chemosynthetic bacteria, especially how the host recognizes symbionts, have remained largely unsolved. In the present study, a modified pull-down assay was conducted using enriched symbiotic methane-oxidation bacteria as bait and gill proteins of Bathymodiolus platifrons as a target to isolate pattern recognition receptors involved in the immune recognition of symbionts. As a result, a total of 47 proteins including BpLRR-1 were identified from the pull-down assay. It was found that complete cDNA sequence of BpLRR-1 contained an open reading frame of 1479 bp and could encode a protein of 492 amino acid residues with no signal peptide or transmembrane region but eight LRR motif and two EFh motif. The binding patterns of BpLRR-1 against microbial associated molecular patterns were subsequently investigated by surface plasmon resonance analysis and LPS pull-down assay. Consequently, BpLRR-1 was found with high binding affinity with LPS and suggested as a key molecule in recognizing symbionts. Besides, transcripts of BpLRR-1 were found decreased significantly during symbiont depletion assay yet increased rigorously during symbionts or nonsymbiotic Vibrio alginolyticus challenge, further demonstrating its participation in the chemosynthetic symbiosis. Collectively, these results suggest that BpLRR-1 could serve as an intracellular recognition receptor for the endosymbionts, providing new hints for understanding the immune recognition in symbiosis of B. platifrons . Highlights: A modified MOB pull-down assay was conducted to isolate symbiosis-related PRRs. BpLRR-1 was identified and proved with high binding affinity with LPS using SPR. Transcripts of BpLRR-1 decreased significantly during symbionts depletion. Robust increase of BpLRR-1 was found after symbionts or Vibrio challenge. BpLRR-1 was suggested as an intracellular recognition receptor for MOB symbionts.